Attractive versus repulsive interactions in the Bose-Einstein condensation dynamics of relativistic field theories - Berges, Jürgen; Boguslavski, Kirill; Chatrchyan, Aleksandr; Jaeckel, Joerg (Physical review, 2017)
We study the impact of attractive self-interactions on the nonequilibrium dynamics of relativistic quantum fields with large occupancies at low momenta. Our primary focus is on Bose-Einstein condensation and nonthermal fixed points in such systems. For a model system, we consider O(N)-symmetric scalar field theories. We use classical-statistical real-time simulations as well as a systematic 1/N expansion of the quantum (two-particle-irreducible) effective action to next-to-leading order. When the mean self-interactions are repulsive, condensation occurs as a consequence of a universal inverse particle cascade to the zero-momentum mode with self-similar scaling behavior. For attractive mean self-interactions, the inverse cascade is absent, and the particle annihilation rate is enhanced compared to the repulsive case, which counteracts the formation of coherent field configurations. For N≥2, the presence of a nonvanishing conserved charge can suppress number-changing processes and lead to the formation of stable localized charge clumps, i.e., Q balls.